STUDY OF LYSINE AND ALANINE DELIVERANCE THROUGH POLYPYRROLE MEMBRANE - Adhitasari Suratman; Buchari Buchari; Indra Noviandri; Suryo Gandasasmita (Indonesian Journal of Chemistry, 2004)
Electropolymerization processes of pyrrole and the usage of polypyrrole membrane as lysine and alanine deliverance have been studied by cyclic voltammetry technique. Polypyrrole membrane was prepared by electropolymerization processes of pyrrole in water based solvent containing sodium perchlorate as supporting electrolyte. Electropolymerization processes were carried out within potential range of 0-1100 mV vs Ag/AgCl reference electrode and at the scanning rate of 100 mV/s. In this study, lysine and alanine have been used as molecules which could easily be loaded on and released from polypyrrole membrane. The presence of lysine or alanine during electropolymerization process reduced the rate of electropolymerization of polypyrrole. In lysine or alanine transfer processes into polypyrrole membrane, the interaction between polypyrrole and lysine or alanine showed by the curve of E½ oxidation in respect of - log C. It proved that the E½ oxidation shifted to more positive potential showed by the increasing of concentration of lysine or alanine. Beside that, voltammetric responses of lysine and alanine transfered into polypyrrole membrane were found to be Nernstian. The results indicated that polypyrrole could be used as a sensor of lysine and alanine.